Cutibacterium acnes biofilm formation is influenced by bone microenvironment, implant surfaces and bacterial internalization - Jennifer Varin-Simon; Marius Colin; Frédéric Velard; Min Tang-Fichaux; Xavier Ohl; Céline Mongaret; Sophie C. Gangloff; Fany Reffuveille (BMC Microbiology)
Abstract Background The bacterial persistence, responsible for therapeutic failures, can arise from the biofilm formation, which possesses a high tolerance to antibiotics. This threat often occurs when a bone and joint infection is diagnosed after a prosthesis implantation. Understanding the biofilm mechanism is pivotal to enhance prosthesis joint infection (PJI) treatment and prevention. However, little is known on the characteristics of Cutibacterium acnes biofilm formation, whereas this species is frequently involved in prosthesis infections. Methods In this study, we compared the biofilm formation of C. acnes PJI-related strains and non-PJI-related strains on plastic support and textured titanium alloy by (i) counting adherent and viable bacteria, (ii) confocal scanning electronic microscopy observations after biofilm matrix labeling and (iii) RT-qPCR experiments. Results We highlighted material- and strain-dependent modifications of C. acnes biofilm. Non-PJI-related strains formed aggregates on both types of support but with different matrix compositions. While the proportion of polysaccharides signal was higher on plastic, the proportions of polysaccharides and proteins signals were more similar on titanium. The changes in biofilm composition for PJI-related strains was less noticeable. For all tested strains, biofilm formation-related genes were more expressed in biofilm formed on plastic that one formed on titanium. Moreover, the impact of C. acnes internalization in osteoblasts prior to biofilm development was also investigated. After internalization, one of the non-PJI-related strains biofilm characteristics were affected: (i) a lower quantity of adhered bacteria (80.3-fold decrease), (ii) an increase of polysaccharides signal in biofilm and (iii) an activation of biofilm gene expressions on textured titanium disk. Conclusion Taken together, these results evidenced the versatility of C. acnes biofilm, depending on the support used, the bone environment and the strain.